Donor human milk programs in German, Austrian and Swiss neonatal units - findings from an international survey - Daniel Klotz; Stefanie Jansen; René Glanzmann; Nadja Haiden; Hans Fuchs; Corinna Gebauer (BMC, 2020)
Abstract Background Donor human milk (DHM) has been recommended for premature infants if mothers' own milk is not available. The aim of this study was to increase the knowledge about the utilization rate and handling of DHM among neonatal units in Germany, Austria und Switzerland. Methods Online survey of utilization rates and handling practices of DHM of all neonatal units within Germany, Austria and Switzerland providing care for premature infants less than 32 weeks of gestation. Results DHM utilization rate of 35% is low (50/142) within those 54% of units that responded to our survey (142/261). Only 26/50 units have DHM routinely integrated into their nutritional management protocols. Lacking access and difficult procurement were cited as the main obstacles for not using DHM. However, eight out of ten respondents currently not using DHM would like to introduce DHM in their unit if available. There were differences in most aspects of DHM handling including donor recruitment and screening, testing and treatment of milk microbiota and commencement of DHM utilization. Breastmilk feeding rates were increased in units utilizing DHM compared to those not utilizing DHM. Conclusions DHM is underutilized in most neonatal units caring for premature infants within participating countries. Lacking access to DHM represents the main barrier for utilizing DHM for premature infants.